1994
DOI: 10.1177/002199839402800503
|View full text |Cite
|
Sign up to set email alerts
|

Shape Control of Composite Plates and Shells with Embedded Actuators. I. Voltages Specified

Abstract: The changes in shapes of fiber-reinforced composite beams, plates and shells affected by embedded piezoelectric actuators were investigated. An analytical method was developed which can be used to calculate the changes in shapes for specified applied voltages to the actuators. The method is formulated on the basis of mathematical models using two-dimensional, linear, shallow shell theory including transverse shear effects which are important in the case of sandwich construction. Solutions to the governing equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(49 citation statements)
references
References 30 publications
5
44
0
Order By: Relevance
“…2. Good agreement is seen between the numerical results of current study with the experimental results of (Koconis et al 1994). …”
Section: Verification Studiessupporting
confidence: 83%
See 1 more Smart Citation
“…2. Good agreement is seen between the numerical results of current study with the experimental results of (Koconis et al 1994). …”
Section: Verification Studiessupporting
confidence: 83%
“…The material properties of the Kynar layer are given in (Shakeri et al 2009). The effect of applied voltage on the deflection of the free end of the beam is investigated by (Koconis et al 1994) and are compared with the present study results in Fig. 2.…”
Section: Verification Studiesmentioning
confidence: 78%
“…The e ects of applied voltage on the tip de ection are studied and compared with the results obtained by Koconis et al [32] in Figure 3. It is observed that results obtained by the present model are in excellent agreement with those of Koconis et al [32]. Having validated our proposed model, we present in this section results of static and dynamic studies on FGM plates with integrated piezoelectric sensor and actuator layers for two distinct conÿgurations.…”
Section: Numerical Studiesmentioning
confidence: 94%
“…The relevant material properties are listed in Table I. The e ects of applied voltage on the tip de ection are studied and compared with the results obtained by Koconis et al [32] in Figure 3. It is observed that results obtained by the present model are in excellent agreement with those of Koconis et al [32].…”
Section: Numerical Studiesmentioning
confidence: 99%
“…In particular, active buckling (Chandrashekhara and Bhatia, 1993) and shape control (Koconis, Kollar and Springer, 1994a;1994b) have been considered. The application of piezoelectric devices to active vibration control of plates has focused on relatively low frequency modes afforded by thin plates (Tanaka, Kikushima and Kuroda, 1992).…”
Section: Finite Element Modeling Of a Photolithography Platenmentioning
confidence: 99%